TUNING TO ROAD AND LOAD PASSIVE SUSPENSIONS MULTI-MODELLING AND OPTIMISATION - Ciprian Tabacu; Lucian Dan Campan (European Scientific Journal, ESJ, 2013)
This work explores the ability to apply multi-modeling technique of new suspension system based on a shock absorber model VZN (European Patent 1190184/20052). Here are presented the results of their own scientific research on the multi-modelling a auto vehicles suspension systems based on passive hydraulic shock absorbers with variable damping characteristics depending on the position of the sprung mass and road conditions. For such a system was proposed and verified by in Matlab-Simulink simulation, a procedure for optimizing the damping characteristics of the road conditions and load given. Suspension system is represented by a quarter-car multi-model with one degree of freedom and representative way perturbation by white noise. Proposed new criterion function in optimisation self-adaptive passive suspension.